Beauty and persuasión in Plato's ,Phaedrus and Aristóteles Rethoric (Iter, 2022)
In this article. beauty> and discourse are studied from the viewpoint of rhetoric in both Platoand Aristotle. While in the former these aspects are considered in the perspective of aphilosophical rhetoric. strongly committed to the knowledge of goodness and truth. in thelatter emphasis is given on the rhetoric as an art. independently of epistemic and moralcriterio. Despite of this difference. there are some common components too. especially inrespect of their idea of beauty. which allon s us to realice a certain continuity beween the masterand the disciple.
Keywords: Plato. Aristotle. rhetoric. beauty\ discourse